Vozes indígenas: entre apagamentos, estigmas e resistências - discursos midiáticos da região Norte do Brasil sobre povos e lideranças indígenas - Rubim, Deyse Silva (2021)
In order to understand the meanings arising from the media circulation referring to indigenous voices in the northern region of Brazil, we analyze the interfaces of the discourse with the different manifestations emerging in the traditional press, alternative press and social networks. How and when the voices of indigenous people are presented or not by the media from the 1990s to the present. To this end, the clippings that make up the corpus of this study were taken from the newspaper (printed and digital) A Crítica, from the journalistic agency Amazônia Real and from the social network Facebook. The hypothesis was raised that media discourses in the Northern Region in the 90s, consist of silences that corroborate the idea of tutelage (control and power), making indigenous re-democratization invisible through the erasure of these voices. In contrast to this, in the 2000s, indigenous voices began to have a place in the digital press, more specifically, in the alternative press. There are voices to consolidate the resistance process historically marked by conflicts of exclusion, in this way, indigenous female leaders are also inscribed in discursive practices. In addition, social networks function as a space for the legitimacy of voices and the articulation of indigenous movements. However, despite the protagonism of the indigenous people in political and social mobilizations, the preservation of old memories that produce silences and stigmas, and transformations, above all, with the resistant appropriation of an ephemeris and technologies conceived by non-indigenous people continue to reproduce the prejudice discourse until today. In this sense, the general objective of the research was to identify the relations of discourse and power in media representations from the 90s to the present. For this, some specific objectives were established that guided the research: i) to analyze the heterogeneity of the discourse and the discursive memory with regard to the erasure of the indigenous voices in the media discourses; ii) understand how some linguistic markings corroborate the stigmatization and silencing of indigenous people in the discourse; iii) describe the process of enrolling the voices of female leaders in discursive practices. The theoretical and methodological assumptions that support this research are those of Discourse Analysis of French orientation, with which we propose to analyze how the media from the 90s until today, examining its function as a kind of spokesperson who (re)says the sayings of the indigenous people or, in certain moments, barely presents them as protagonists of their actions. Therefore, in return for a greater conservation of discriminatory discourses, based on mobilizations to guarantee their rights and supported by cultural dynamics that allowed access to different forms of communication, today, the indigenous people (leaders, women and young people) take the floor, they assume their place of representative speech and occupy legitimate spaces in Brazilian society.